Pengalaman Mahasiswa Keperawatan Anestesiologi yang Pertama Kali Akan Menjalani Praktik di Rumah Sakit - Tanamal, Uswatun Chasana; Firdaus, Eza Kemal; Yanti, Linda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study examined the experiences of anesthesiology nursing students during their first clinical experience. Students often feel unprepared, anxious, and afraid of making mistakes, due to a lack of mastery of theory and practice, as well as concerns related to trust from anesthesia administrators. This study used a qualitative method with a phenomenological approach. i.e. the researcher identifies the essence of the participant's experience of a phenomenon experienced. This study found that nursing students experience significant stress during their initial clinical practice. This stress is caused by the new environment, fear of making mistakes, and pressure from senior staff, which can negatively affect their mood, health, and relationships. However, stress can also motivate students to learn and improve their skills. This study concluded that nursing students in anesthesiology experience a range of emotions during their initial hospital practice. Initially, they faced negative feelings such as anxiety and lack of confidence, which manifested as physical symptoms such as nervousness and confusion. However, these challenges are mitigated through positive thinking and preparation, leading to personal growth and self-esteem after practice.